Four-Port Dual-Mode Diplexer with High Signal Isolation. (10th February 2020) - Konpang, Jessada; Wattikornsirikul, Natchayathorn
Abstract : An ease of four-port dual-mode diplexer with high signal isolation is presented. A compact dual-mode diplexer with high signal isolation between the Rx and Tx modules is achievable by only using one resonator filter topology. Two back-to-back dual-mode diplexers have a 180° phase shift in one branch. The high isolation can be achieved by amplitude and phase cancellation technique. The delayed transmission line can be easily achieved by the phase shifter. The simulated and measured four-port dual-mode diplexers are designed at the centre frequency of Rx/Tx at 1.95 GHz and 2.14 GHz, respectively. The measured results of Rx/Tx dual-mode diplexer devices are presented with 47.1 dB Rx/Tx isolation. This four-port dual-mode diplexer achieves the isolation ( S 32 ) of more than 24.1 dB when compared with the conventional three-port dual-mode diplexer structure.